ANALYSIS OF PUBLIC PERCEPTION AND INTEREST IN THE DECISION TO CHOOSE ACCOUNTING MAJOR - Hendi Prihanto; Watriningsih Watriningsih (Universitas Pamulang, 2018)
This study aims to find out the influence of public perception and interest on the decision to choose accounting major. The population of the study is high schools in Kebayoran Baru. The data is collected using clusters in South Jakarta. The data is obtained by distributing questionnaires to the students in twelfth grade who will continue their study to higher education. This study applies quantitative method with causal relationship to determine the influence of the independent variables (perception and interest) on the dependent variable (public decision to choose accounting department). Research findings show that the perception and interest partially influence the decision to choose in positive and significant manner.